The Mycobacterium tuberculosis membrane protein Rv0180c: Evaluation of peptide sequences implicated in mycobacterial invasion of two human cell lines (2011)
The identification and characterization of hypothetical membrane proteins from Mycobacterium tuberculosis have led to a better understanding of the mechanisms used by this pathogen to invade and survive inside host cells. This study assessed the presence, transcription, localization and possible biological activity of the conserved hypothetical protein Rv0180c from M. tuberculosis. Bioinformatics analyses indicated that Rv0180c contains a signal peptide, six possible transmembrane helices and a Plasmodium Export Element (PEXEL)-like motif. PCR analyses showed the presence of the Rv0180c gene in strains from the M. tuberculosis complex; but transcription was not detected in Mycobacterium microti. Sera against synthetic peptides of Rv0180c recognized two protein bands in M. tuberculosis H37Rv sonicate: a ?48-kDa band close to the predicted molecular mass of Rv0180c (47.6 kDa), and a 63-kDa band probably caused by protein modifications. Moreover, the same sera located the protein on the surface of M. tuberculosis H37Rv bacilli by immunoelectron microscopy. Twenty-three synthetic peptides spanning the entire length of Rv0180c were tested for their ability to bind to U937 and A549 cells, finding nine high-activity binding peptides (HABPs) specific for both cell types, two HABPs specific for A549 cells (namely 31032 and 31044) and two HABPs specific for U937 cells (namely 31025 and 31041). HABPs inhibited invasion of M. tuberculosis H37Rv into A549 or U937 cells by significant percentages and facilitated internalization of latex beads in A549 cells. The Rv0180c HABPs herein reported could be preliminary candidates to be assessed as components of a multiepitope, chemically synthesized, subunit-based vaccine against tuberculosis. © 2010 Elsevier Inc. All rights reserved.